Medicine‐taking experiences and associated factors: comparison between Arabic‐speaking and Caucasian English‐speaking patients with Type 2 diabetes. Issue 12 (28th April 2015) - Alzubaidi, H.; Mc Mamara, K.; Chapman, C.; Stevenson, V.; Marriott, J.
Abstract: Aim: The aim of this study was to explore and compare medication‐taking experiences and associated issues in Arabic‐speaking and Caucasian English‐speaking patients with Type 2 diabetes in Australia. Methods: Various healthcare settings in metropolitan Melbourne, Australia, were purposefully selected to obtain a diverse group of participants with Type 2 diabetes. Recruitment occurred at diabetes outpatient clinics in two tertiary referral hospitals, six primary care practices and ten community centres. Face‐to‐face semi‐structured individual interviews and group interviews were employed. All interviews were audiotaped, transcribed and coded thematically. Data collection continued until saturation was reached. Results: In total, 100 participants were recruited into two groups: 60 were Arabic‐speaking and 40 were Caucasian English‐speaking. Both groups had similar demographic and clinical characteristics. Only 5% of the Arabic‐speaking participants had well‐controlled diabetes compared with 17.5% of the participants in the English‐speaking group. Arabic‐speaking participants actively changed medication regimens on their own without informing their healthcare professionals. Arabic‐speaking patients had more knowledge gaps about their prescribed treatments, compared with the English‐speaking group. Their use of diabetes medicines was heavily influenced by peers with diabetes and family members; conversely, they feared revealing their diagnosis within the wider Arabic community due to stigma and collective negative social labelling of diabetes. Confidence in non‐Arabic‐speaking healthcare providers was lacking. Conclusions: Findings yielded new insights into medication‐taking practices and associated factors in Arabic‐speaking patients with diabetes. It is vital that healthcare professionals working with Arabic‐speaking patients adapt their treatment approaches to accommodate different beliefs and views about medicines. What's new?: This paper reports the first study to explore medication‐taking experiences and associated issues in Arabic‐speaking patients with diabetes and compare them with Caucasian English‐speaking patients (representing mainstream society). Arabic‐speaking immigrants reported unique cultural beliefs, which impacted negatively on their medication‐taking behaviours. When describing collective negative social labelling for people with diabetes, Arab immigrants were gender‐specific. Participants changed medication regimens on their own, without informing their healthcare professionals. Findings yielded new insights on medication‐taking practices of Arabic‐speaking patients with diabetes. It is vital that diabetes healthcare professionals working with Arabic‐speaking patients to adapt their treatment approaches to accommodate different beliefs and views about medicines.